An alternative mini buffy coat preparation method for adult patients with extracorporeal photopheresis contraindications. Issue 1 (4th March 2016) - Grabmer, Christoph; Schlager, Sandra; Mayer, Georg; Streif, Doris; Lener, Thomas; Schallmoser, Katharina; Rohde, Eva
Abstract : Background : Extracorporeal photopheresis (ECP) is an important cell‐based therapy for various diseases but is limited to patients eligible for apheresis. We developed an alternative mini buffy coat (BC) preparation method using the Spectra Optia® apheresis system and compared its efficacy of white blood cell (WBC) recovery with the standard mini BC preparation method already established for pediatric patients.Methods : Whole blood (450 ± 45 mL) samples were collected from 30 randomly selected healthy volunteer blood donors and divided into two groups. In the first group, WBCs were separated with a fully automated separator device (Compomat G4 ® ). In the second group, BCs were separated with the bone marrow processing program of the Spectra Optia apheresis system.Results : There were no significant differences in total leukocyte counts per product between the two groups. In contrast, lymphocyte counts per product were significantly higher ( P < 0.001) in BCs separated from apheresis.Conclusion : Our novel technique resulted in similar WBC yields but higher lymphocyte yields than the standard mini BC preparation method. This method can serve as an alternative to WBC collection in conventional ECP for adult patients with apheresis contraindications. J. Clin. Apheresis 32:12–15, 2017. © 2016 Wiley Periodicals, Inc.